A temporal analysis on patient and health service delays in pulmonary tuberculosis in Portugal: inter and intra‑regional differences and in(equalities) between gender and age - Chakma, Bhaswar (2022)
An exploratory analysis was performed, trends of both delays were studied, and 36 months forecasts were generated. We used the permutation test to test differences between groups and the Seasonal and Trend decomposition using Loess (STL) method and Autoregressive Integrated Moving Average (ARIMA) models for forecasting for both Health and Patient delays. We used data from notified PTB cases in mainland Portugal between 2008 and 2017, provided by the national surveillance system.